Review and Analysis of Speech Recognition Techniques for Mobile Devices - Dharmale, Gulbakshee J; Patil, Dipti D; Thakare, Vilas M (International Journal of Computer Sciences and Engineering, 2019)
The most widely correspondence modes for individuals is speech. People use speech as another mode to convey information without lifting a finger with the help of speech recognition applications. This paper presents a study about execution of speech recognition debilitates inside considering resounding and even low levels of including clamor. Speech recognition interfaces in local lingo which connects the people to use the advancement to more imperative degree without the data by operating with a PC. An extraordinary measure of research has done in different areas of speech recognition and its applications since three decades. A specific overlook on speech recognition has been done in this paper, introducing the design, databases, speech parameterization, techniques, attributes, apparatuses, applications and issues. Also analyzed performance with respective accuracy for different available techniques from various research work.